Enhancing Student Engagement and Learning Outcomes through Interactive Approaches in College Vocal Music Instruction - CAO, JIAKAI (Pacific International Journal, 2024)
This study investigates the enhancement of student engagement and learning outcomes in college vocal music instruction at Bozhou University, Anhui Province, China, through the implementation of interactive approaches. Recognizing the pivotal role of music education in shaping artistic and academic development, the research addresses the current challenges in student engagement and identifies the pressing need for innovative instructional strategies. The study employs a qualitative research design, conducting in-depth interviews with 25 undergraduate students to explore their perceptions of current vocal music instruction and the impact of interactive methodologies. Findings reveal diverse student perspectives on teaching methods, engagement levels, collaborative learning, technology integration, and assessment processes. The study highlights the potential of interactive elements, such as active learning strategies and technology-assisted instruction, to positively influence student engagement. Furthermore, it explores the implications of interactive approaches on learning outcomes, emphasizing holistic skill development and leveraging technology for effective learning facilitation. The discussion outlines practical implications for curriculum design, educator professional development, and the creation of a supportive learning environment. The findings contribute valuable insights to the ongoing discourse on effective music education strategies, providing a foundation for curriculum refinement and innovation in the evolving landscape of collegiate music education.